Perceptions of co-teaching as a pedagogical approach to integrate basic and clinical sciences - Rodríguez-Martín, Ivan; Condés, Emilia; Sánchez-Gómez, Judit; Azpeleta, Clara; Tutor, Antonio S.; Lesmes, Marta; Gal, Beatriz (Frontiers in Medicine, 2024)
BACKGROUND: Medical curricula must provide students with basic and clinical competencies for critical reasoning and diagnosing. These competencies are better acquired when basic and clinical science are taught in an integrated and collaborative manner. In this study, we investigate whether supportive co-teaching (SCT) is an effective approach to promote integrated and reasoned learning as well as to help medical students applying theoretical concepts to clinical scenarios taught in a team-based learning (TBL) framework.We conducted a concurrent mixed methods study. For the qualitative part, we performed a focus group and semi-structured interviews to clinical and basic science teachers and medical students. Using conventional content analysis, themes were identified deductively. For the quantitative part, an analytical and descriptive observational study of the 2019-2020 cohort of first-year undergraduate medical students was conducted (107 students out of 220 completed the survey). For the descriptive study, questions were grouped into 5 categories.Deductive themes from the analysis include relationship between clinical and basic science teachers, knowledge integration, methodology, teamwork and integrated Medicine and curricular design. Basic science and clinical teachers highlighted their relationship as critical to increase their mutual knowledge. This was supported by the student´s opinion who very much valued their joint feedback. Regarding knowledge integration, both teachers and students found that horizontal and vertical integration enhanced applicability of basic knowledge to future clinical practice. The TBL methodology was very well perceived by both students and teachers and was highly motivating for students even though the need for commitment. Students considered that this program presented a great opportunity and expressed their interest in maintaining it in the future. These results were supported by the quantitative data.Our work supports the value of co-teaching in basic and clinical sciences within a TBL framework set in real clinical case scenarios. By employing this approach, students can actively apply their theoretical knowledge to clinical practice, enhancing their critical thinking, problem-solving, and clinical reasoning skills. Our findings can inform curriculum design and improved educational practice, leading to enhanced learning experiences for healthcare students and ultimately better patient care.